DETERMINANTS OF CASHLESS PAYMENT ADOPTION AMONG RURAL RESIDENTS IN SUNGAI PETANI, KEDAH - Khairol, Nur Liyana Izzati Mohamad; Anuar, Nur Khairunnisa Khairol; Abidin, Nor Zaini Zainal (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
Cashless payment methods have revolutionized transactions in the world today. As a new way of spending money became widespread, the situation resulted in an increase in the use of electronic wallets, internet banking, and contactless card payment. The increasing importance of technology for everyday business operations is represented in the growing reliance on digital financial services. However, the level of adoption of cashless payments in rural communities remains an important area of investigation. Despite the growing adoption of cashless payment systems, there is still a limited understanding of how infrastructure, digital literacy, trust, and merchant readiness collectively influence actual usage in rural areas, particularly in developing countries. This study aims to examine the determinants influencing the adoption of cashless payment systems in selected rural areas of Sungai Petani, Kedah. Data was collected from respondents living in rural communities and analyzed using the Statistical Package for the Social Sciences (SPSS). The analysis was conducted to determine the relationship between several selected variables and the adoption of cashless payment methods among rural residents. The findings indicate that a number of factors influence the adoption of cashless payment systems in rural areas. In addition, the results highlight the important role of technological advancement and accessibility in encouraging individuals to adopt digital payment platforms. The study also suggests that increased awareness and exposure to digital financial services can further promote the use of cashless payments. Overall, the findings provide useful insights for policymakers, financial institutions, and service providers in developing strategies to enhance digital payment adoption and promote financial inclusion in Malaysia.